Konstelasi Politik Internasional: Dimanakah Posisi Indonesia? - Q.A., Siti Amelia (Global and Policy Journal of International Relations, 2013)
ABSTRACTInternational constellation is the structure of international relations that influence, which is the conditions surrounding the first country and the countries that compete with it. International constellation, not relate to the idea and implementation methodology of the politics (ideology), but it relates with international relations and permanent competition among countries to achieve as the first position country and to influence international politics. International constellation is not fixed, but change, and the changing according to different situations, conditions and world events.Keywords : Constellation, International Politics, Indonesian PoliticDOI:https://doi.org/10.33005/jgp.v1i01.2011